WNK1/HSN2 founder mutation in patients with hereditary sensory and autonomic neuropathy: A Japanese cohort study. Issue 6 (20th July 2017) - Yuan, J.‐H.; Hashiguchi, A.; Yoshimura, A.; Sakai, N.; Takahashi, M.P.; Ueda, T.; Taniguchi, A.; Okamoto, S.; Kanazawa, N.; Yamamoto, Y.; Saigoh, K.; Kusunoki, S.; et al.
Abstract : The clinical and genetic spectrum of hereditary sensory and autonomic neuropathy (HSAN) is still unknown in Japan. We collected a broad cohort of 33 unrelated patients with predominant sensory and/or autonomic dysfunctions, who were referred to our genetic laboratory. A gene panel sequencing targeting 18 HSAN‐related genes was performed using a next‐generation sequencing system. A recurrent frame shift mutation in the WNK1/HSN2 gene, c.3237_3238insT (p.Asp1080*), was detected in 5 patients. This mutation was homozygous in 4 cases and of a compound heterozygous genotype in 1 case. Geographic and haplotype analysis of all 5 patients suggested a founder event. In addition, a novel heterozygous nonsense variant, c.2615C>G (p.Ser872*), was identified. All the 5 patients presented with severe sensory and autonomic dysfunctions at birth or during adolescence. In 2 patients, an uncommon phenotype of acute pathological pain presented at 50 years of age. Here, we present the first founder mutation of WNK1/HSN2, in addition to French Canadian, which accounts for 15.2% of Japanese patients with HSAN in our cohort. We have also reviewed all previously described mutations in WNK1/HSN2 and reconciled their nomenclature strategy on the basis of the current longest transcript. Abstract :